2014
DOI: 10.5430/wjel.v4n1p9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Computer-Mediated Communication Environments on Foreign Language Learning: A Review of the Literature

Abstract: This article reviews the literature on the implementation of computer-mediated communication (CMC) in language learning. This review aims at understanding how CMC environments have been implemented to foster language learning. The review draws on 40 recent research articles selected form 10 peer-reviewed journals, 2 book chapters and one conference proceeding. This review investigates the studies that have dealt with the CMC environments used for language learning. It reviews the studies that have explored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
(13 reference statements)
3
16
0
Order By: Relevance
“…More importantly, it was used by students to carry their conversations in the computer lab. However, these results are in line with Mahdi (2014) who indicated that using Skype for the oral CMC group created turn-taking patterns that were very close to face-to-face turn taking.…”
Section: Questionsupporting
confidence: 80%
“…More importantly, it was used by students to carry their conversations in the computer lab. However, these results are in line with Mahdi (2014) who indicated that using Skype for the oral CMC group created turn-taking patterns that were very close to face-to-face turn taking.…”
Section: Questionsupporting
confidence: 80%
“…The dynamic development of internet technologies has affected many aspects of life including in education and even in the language classroom. The use of these technologies has been reported to make language learning become more effective [2]. Consequently, online learning is rapidly permeating EFL/ESL courses in the past two decades [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of online discussion platforms; synchronous discussions require the interlocutors to be logged in simultaneously whereas asynchronous communication does not have specific limitations in terms of time and place [2]. One online platform which offers a space for online discussion is Facebook through its Messenger facility.…”
Section: Introductionmentioning
confidence: 99%
“…Using technology in language learning is the topic of several studies (for review see Golonka, et al 2014;Mahdi, 2014). These studies have revealed a number of encouraging results which indicated that language learning with the help of technology can be more effective than through the use of traditional ways.…”
Section: Introductionmentioning
confidence: 99%